2001
DOI: 10.1289/ehp.01109903
|View full text |Cite
|
Sign up to set email alerts
|

Brominated flame retardants: a novel class of developmental neurotoxicants in our environment?

Abstract: Brominated flame retardants are a novel group of global environmental contaminants. Within this group the polybrominated diphenyl ethers (PBDE) constitute one class of many that are found in electrical appliances, building materials, and textiles. PBDEs are persistent compounds that appear to have an environmental dispersion similar to that of polychlorinated biphenyls (PCBs) and dichlorodiphenyltrichloroethane (DDT). Levels of PBDEs are increasing in mother's milk while other organohalogens have decreased in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
389
1
5

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 534 publications
(414 citation statements)
references
References 40 publications
19
389
1
5
Order By: Relevance
“…Control mice display habituation, a decrease in locomotion, rearing and total activity variables in response to the diminishing novelty of the test chamber over 60-min. Thus, the investigators interpret their results (initial hypoactivity and late hyperactivity) as a decrease in habituation caused by PBDEs (Eriksson et al 2001). An alternative interpretation might be that the decreased activity at the beginning of the session is a possible sign of increased anxiety or arousal, and the elevated activity later in the session is simply the animals finally beginning to explore their environment, as controls did at the beginning of the session.…”
Section: Behavioral Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Control mice display habituation, a decrease in locomotion, rearing and total activity variables in response to the diminishing novelty of the test chamber over 60-min. Thus, the investigators interpret their results (initial hypoactivity and late hyperactivity) as a decrease in habituation caused by PBDEs (Eriksson et al 2001). An alternative interpretation might be that the decreased activity at the beginning of the session is a possible sign of increased anxiety or arousal, and the elevated activity later in the session is simply the animals finally beginning to explore their environment, as controls did at the beginning of the session.…”
Section: Behavioral Studiesmentioning
confidence: 99%
“…A Swedish group has carried out most studies on developmental neurotoxicity of various PBDEs (see Table 7; Eriksson et al 2001;Viberg et al 2003a;2003b;2007a). Their experimental protocol involves direct exposure of neonatal mice or rats to PBDEs, as a single oral dose, usually on post-natal day (PND) 10.…”
Section: Behavioral Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies with experimental animals have indicated that pre-and postnatal exposure to PBDEs impairs motor activity and cognitive behavior. Exposure of neonatal rats to BDE-47 (the most prominent PBDE congener in CSF and cerebellum GM) caused poor performance in horizontal locomotor activity (Eriksson et al, 2001). In addition to the effects on the cerebellum, exposure of neonatal rats to some PBDEs (e.g., BDE-153) impairs learning and memory and decreases hippocampal cholinergic receptors (Viberg et al, 2003).…”
Section: Brominated Flame Retardants and Oh-pbdesmentioning
confidence: 99%
“…The most prominent PBDE congeners found in the environment, humans, birds of prey and other wildlife are BDE-47, BDE-99, and BDE-100 (Eriksson et al, 2001;Chen and Hale, 2010;Nilsen et al, 2014-in this issue), with some inter-regional differences. At sites furthest downstream on the LCR, sperm quality values in LSS were the lowest.…”
Section: Fish and Sitesmentioning
confidence: 93%